Unilateral hyperkeratotic dark plaques covering the entire right lower extremity: A rare entity - Bostan, Ecem; Yalici-Armagan, Basak; Yel, Beril; Gokoz, Ozay (Acta Medica, 2022)
Verrucous venocapillary malformation, formerly known as verrucous hemangioma, presents itself as single or multiple, well-demarcated, erythematous plaques that eventually acquire hyperkeratinization, oozing, bleeding and become thicker and darker over time. We report a case of verrucous venocapillary malformation in 33-year old woman referred to the dermatology outpatient clinic with the complaint of hyperkeratotic plaques covering the entire right leg and thigh, present since birth.